Urban transition through Indonesian art: from the Generation of '66 to the Millennials. Issue 2 (4th May 2021) - Jurriëns, Edwin
Abstract : This article discusses the representation of Jakarta and other cities in the work of Indonesian visual artists. These artists document not only urban landscapes as such, but also the ideas, lifestyles and creative forms of expression of different generations of Indonesians, including artists themselves. I argue that the urban visualisations demonstrate the opportunities for and limits to social engagement in Indonesian art at different points in time. They also provide insight into the relevance of the very idea of a 'generation' in Indonesian social and intellectual history. I examine in detail how S. Sudjojono's urban paintings have visualised Jakarta's changing material infrastructure in the 1960s, the emergence of visual artists and literary authors who would become known as the 'Generation of '66, ' as well as the artist's doubts about his own artistic and ideological development. I compare his work with the representation of Jakarta's intensified urbanisation in the 1970s and 1980s in the paintings of Srihadi Soedarsono and Dede Eri Supria. I also examine how other artists and art collectives from the same period expressed social commitment through spatial interventions and creative collaborations with local communities, NGOs and governments. Finally, I examine artists and art collectives since the 1990s, who have emerged as both members and critics of the Millennial generation. I specifically focus on the work of Adi Yuswantoro and Agan Harahap, who critically evaluate and visually refer to the art and ideals of Sudjojono.